Tantalum-doped zirconium oxychloride lithium solid electrolyte and synthesis method thereof

Through the solid electrolyte of zirconium oxychloride doped with tantalum oxidation lithium oxychloride Li1.75-XZrTa0.2XCl4.75O0.5, the problems of low oxygen conductivity of lithium lanthanum zirconium and safety hazards of liquid batteries are solved, and high ionic conductivity and low cost are achieved The solid electrolyte improves safety performance.

CN119191345APending Publication Date: 2024-12-27SHANDONG XINWEIYUAN NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411319663.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lithium lanthanum zirconium oxygen (LLZO) solid electrolyte has low lithium ion conductivity and cannot meet safety and performance requirements. In addition, liquid lithium ion batteries have hidden dangers of organic combustible substance leakage and combustion explosion.

Method used

Using tantalum doped zirconium oxychloride solid electrolyte Li1.75-XZrTa0.2XCl4.75O0.5, the raw materials with high ionic conductivity is obtained by grinding and ball milling the raw materials under the protection of argon. The value range of X is obtained. It is 0

Benefits of technology

The ion conductivity of room temperature reaches 10-3S/cm, which is 10 times higher than that of metal oxide electrolytes. The manufacturing method is simple, the production cost is low, and the safety performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005053483350000061
    Figure BDA0005053483350000061
  • Figure BDA0005053483350000071
    Figure BDA0005053483350000071
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, in particular to a tantalum-doped zirconium lithium oxychloride solid-state electrolyte and a synthesis method thereof, and the tantalum-doped zirconium lithium oxychloride solid-state electrolyte is composed of Li < 1.75-X > ZrTa < 0.2 > X Cl < 4.75 > O < 0.5 >, wherein the value range of X is more than 0 and less than or equal to 0.15, and the synthesis method comprises the following steps: respectively grinding and sieving a lithium source, a zirconium source and a tantalum source under the protection of argon to obtain 200-mesh raw material fine powder; under the protection of argon, mixing and ball-milling the sieved raw material fine powder according to a stoichiometric ratio to obtain the inorganic solid electrolyte Li < 1.75-X > ZrTa < 0.2 > X Cl < 4.75 > O < 0.5 >; after the obtained solid electrolyte material is subjected to cold pressing to obtain a finished product, the room-temperature ionic conductivity is measured to be 2.41-3.12 * 10 <-3 > S / cm. According to the tantalum-doped zirconium oxychloride lithium solid electrolyte, the normal-temperature ionic conductivity can reach 10 <-3 > S / cm and is about 10 times higher than that of a common metal oxide electrolyte, the manufacturing method is simple, the production cost is low, and expanded production and application are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid-state batteries, and in particular to a tantalum-doped lithium zirconium oxychloride solid-state electrolyte and a synthesis method thereof. Background Art

[0002] Most of the new energy batteries currently used in the market are liquid lithium-ion batteries. Since most of their electrolytes are organic solvents, there are hidden dangers of organic combustible leakage and explosion. Compared with liquid electrolytes, solid electrolytes are composed of solid materials, have a stable crystal structure or amorphous structure, and have higher safety performance.

[0003] Lithium lanthanum zirconium oxide (LLZO) is an important metal oxide solid electrolyte, but its lithium ion conductivity is generally 10 -4 S / cm. Therefore, in view of this situation, it is urgent to develop a tantalum-doped lithium zirconium oxychloride solid electrolyte to overcome the shortcomings in current practical applications. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a tantalum-doped lithium zirconium oxychloride solid electrolyte and a synthesis method thereof to solve the problems raised in the above background technology.

[0005] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:

[0006] A tantalum-doped lithium zirconium oxychloride solid electrolyte, comprising Li 1.75-X ZlUT 0.2X Cl 4.75 O 0.5 ; Wherein, the value range of X is 0<X≤0.15.

[0007] Another object of the present invention is to provide a method for synthesizing a tantalum-doped lithium zirconium oxychloride solid electrolyte, comprising the following steps:

[0008] Step 1, under the protection of argon gas, the lithium source, the zirconium source and the tantalum source are respectively ground and sieved to obtain 200-mesh raw material fine powder;

[0009] The lithium source is LiCl, the zirconium source is ZrCl4 and ZrO2, and the tantalum source is Ta2O5;

[0010] The molar stoichiometric ratio of LiCl, ZrCl4, ZrO2 and Ta2O5 is 1.6-1.7: 0.7625-0.7875: 0.2125-0.2375: 0.005-0.015.

[0011] Step 2: Under the protection of argon gas, the sieved raw material fine powder is mixed and ball-milled according to the stoichiometric ratio to obtain the inorganic solid electrolyte Li 1.75-X ZlUT 0.2X Cl 4.75 O 0.5 ;

[0012] The value range of X is 0<X≤0.15;

[0013] The ball-to-material ratio of the ball mill is 15 to 60:1, preferably 20 to 30:1; the rotation speed of the ball mill is 200 to 1000 rpm, preferably 550 to 600 rpm; the time of the ball mill is 12 to 48 hours, preferably 24 to 36 hours;

[0014] Step 3: After the obtained solid electrolyte material is cold-pressed into a finished product, the ionic conductivity at room temperature (25°C) is measured to be 2.41-3.12×10 -3 S / cm;

[0015] The cold pressing pressure is 20 MPa, and the obtained electrolyte sheet has a diameter of 13 mm and a thickness of 4 mm.

[0016] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:

[0017] The tantalum-doped lithium zirconium oxychloride solid electrolyte provided by the present invention is a new inorganic solid electrolyte with an ionic conductivity of up to 10 at room temperature. -3 S / cm, which is about 10 times higher than that of general metal oxide electrolytes. The manufacturing method is simple and the production cost is low, which is conducive to large-scale production and application. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example 1

[0020] A tantalum-doped lithium zirconium oxychloride solid electrolyte, i.e., an inorganic solid electrolyte, comprising Li 1.7 ZlUT 0.01 Cl 4.75 O 0.5 .

[0021] A method for synthesizing a tantalum-doped lithium zirconium oxychloride solid electrolyte comprises the following steps:

[0022] Step 1: In an argon-protected glove box, the lithium source, zirconium source and tantalum source are ground and sieved respectively with a mortar to obtain 200-mesh raw material fine powder.

[0023] The lithium source is LiCl, the zirconium source is ZrCl4 and ZrO2, and the tantalum source is Ta2O5.

[0024] Step 2: In an argon-protected glove box, the sieved raw material fine powders are mixed and ball-milled in a ball mill according to the stoichiometric ratio to obtain an inorganic solid electrolyte Li 1.75-X ZlUT 0.2X Cl 4.75 O 0.5 powder.

[0025] The value of X is 0.05, and the inorganic solid electrolyte is Li 1.7 ZlUT 0.01 Cl 4.75 O 0.5

[0026] The molar stoichiometric ratio of LiCl, ZrCl4, ZrO2 and Ta2O5 is 1.7:0.7625:0.2375:0.005;

[0027] The ball-to-material ratio of the ball mill is 15:1; the rotation speed of the ball mill is 200 rpm; and the ball milling time is 12 hours.

[0028] Step 3: After the obtained solid electrolyte material is cold-pressed into a finished product, the ionic conductivity at room temperature (25°C) is measured to be 2.41×10 -3 S / cm.

[0029] The cold pressing pressure is 20 MPa, and the obtained electrolyte sheet has a diameter of 13 mm and a thickness of 4 mm.

[0030] Example 2

[0031] A tantalum-doped lithium zirconium oxychloride solid electrolyte, i.e., an inorganic solid electrolyte, comprising Li 1.67 ZlUT 0.016 Cl 4.75 O 0.5 .

[0032] A method for synthesizing a tantalum-doped lithium zirconium oxychloride solid electrolyte comprises the following steps:

[0033] Step 1: In an argon-protected glove box, the lithium source, zirconium source and tantalum source are ground and sieved respectively with a mortar to obtain 200-mesh raw material fine powder.

[0034] The lithium source is LiCl, the zirconium source is ZrCl4 and ZrO2, and the tantalum source is Ta2O5.

[0035] Step 2: In an argon-protected glove box, the sieved raw material fine powders are mixed and ball-milled in a ball mill according to the stoichiometric ratio to obtain an inorganic solid electrolyte Li 1.75-X ZlUT 0.2X Cl 4.75 O 0.5 powder.

[0036] The value of X is 0.08, and the inorganic solid electrolyte is Li 1.67 ZlUT 0.016 Cl 4.75 O 0.5

[0037] The molar stoichiometric ratio of LiCl, ZrCl4, ZrO2 and Ta2O5 is 1.67:0.77:0.23:0.008;

[0038] The ball-to-material ratio of the ball mill is 20:1; the rotation speed of the ball mill is 550 rpm; and the ball milling time is 24 hours.

[0039] Step 3: After the obtained solid electrolyte material is cold-pressed into a finished product, the ionic conductivity at room temperature (25°C) is measured to be 2.87×10 -3 S / cm.

[0040] The cold pressing pressure is 20 MPa, and the obtained electrolyte sheet has a diameter of 13 mm and a thickness of 4 mm.

[0041] Example 3

[0042] A tantalum-doped lithium zirconium oxychloride solid electrolyte, i.e., an inorganic solid electrolyte, comprising Li 1.65 ZlUT 0.02 Cl 4.75 O 0.5 .

[0043] A method for synthesizing a tantalum-doped lithium zirconium oxychloride solid electrolyte comprises the following steps:

[0044] Step 1: In an argon-protected glove box, the lithium source, zirconium source and tantalum source are ground and sieved respectively with a mortar to obtain 200-mesh raw material fine powder.

[0045] The lithium source is LiCl, the zirconium source is ZrCl4 and ZrO2, and the tantalum source is Ta2O5.

[0046] Step 2: In an argon-protected glove box, the sieved raw material fine powders are mixed and ball-milled in a ball mill according to the stoichiometric ratio to obtain an inorganic solid electrolyte Li 1.75-X ZlUT 0.2X Cl 4.75 O 0.5 powder.

[0047] The value of X is 0.1, and the inorganic solid electrolyte is Li 1.65 ZlUT 0.02 Cl 4.75 O 0.5

[0048] The molar stoichiometric ratio of LiCl, ZrCl4, ZrO2 and Ta2O5 is 1.65:0.775:0.225:0.01;

[0049] The ball-to-material ratio of the ball mill is 30:1; the rotation speed of the ball mill is 600 rpm; and the ball milling time is 36 hours.

[0050] Step 3: After the obtained solid electrolyte material is cold pressed into finished product, the ionic conductivity at room temperature (25°C) is measured to be 3.12×10 -3 S / cm.

[0051] The cold pressing pressure is 20 MPa, and the obtained electrolyte sheet has a diameter of 13 mm and a thickness of 4 mm.

[0052] Example 4

[0053] A tantalum-doped lithium zirconium oxychloride solid electrolyte, i.e., an inorganic solid electrolyte, comprising Li 1.63 ZlUT 0.024 Cl 4.75 O 0.5 .

[0054] A method for synthesizing a tantalum-doped lithium zirconium oxychloride solid electrolyte comprises the following steps:

[0055] Step 1: In an argon-protected glove box, the lithium source, zirconium source and tantalum source are ground and sieved respectively with a mortar to obtain 200-mesh raw material fine powder.

[0056] The lithium source is LiCl, the zirconium source is ZrCl4 and ZrO2, and the tantalum source is Ta2O5.

[0057] Step 2: In an argon-protected glove box, the sieved raw material fine powders are mixed and ball-milled in a ball mill according to the stoichiometric ratio to obtain an inorganic solid electrolyte Li 1.75-X ZlUT 0.2X Cl 4.75 O0.5 powder.

[0058] The value of X is 0.12, and the inorganic solid electrolyte is Li 1.63 ZlUT 0.024 Cl 4.75 O 0.5

[0059] The molar stoichiometric ratio of LiCl, ZrCl4, ZrO2 and Ta2O5 is 1.63:0.78:0.22:0.012;

[0060] The ball-to-material ratio of the ball mill is 40:1; the rotation speed of the ball mill is 700 rpm; and the ball milling time is 36 hours.

[0061] Step 3: After the obtained solid electrolyte material is cold pressed into finished product, the ionic conductivity at room temperature (25°C) is measured to be 2.95×10 -3 S / cm.

[0062] The cold pressing pressure is 20 MPa, and the obtained electrolyte sheet has a diameter of 13 mm and a thickness of 4 mm.

[0063] Example 5

[0064] A tantalum-doped lithium zirconium oxychloride solid electrolyte, i.e., an inorganic solid electrolyte, comprising Li 1.6 ZlUT 0.03 Cl 4.75 O 0.5 Synthesis of:

[0065] A method for synthesizing a tantalum-doped lithium zirconium oxychloride solid electrolyte comprises the following steps:

[0066] Step 1: In an argon-protected glove box, the lithium source, zirconium source and tantalum source are ground and sieved respectively with a mortar to obtain 200-mesh raw material fine powder.

[0067] The lithium source is LiCl, the zirconium source is ZrCl4 and ZrO2, and the tantalum source is Ta2O5.

[0068] Step 2: In an argon-protected glove box, the sieved raw material fine powders are mixed and ball-milled in a ball mill according to the stoichiometric ratio to obtain an inorganic solid electrolyte Li 1.75-X ZlUT 0.2X Cl 4.75 O 0.5 powder.

[0069] The value of X is 0.15, and the inorganic solid electrolyte is Li 1.6 ZlUT 0.03 Cl 4.75 O0.5

[0070] The molar stoichiometric ratio of LiCl, ZrCl4, ZrO2 and Ta2O5 is 1.6:0.7875:0.2125:0.015;

[0071] The ball-to-material ratio of the ball mill is 60:1; the rotation speed of the ball mill is 1000 rpm; and the ball milling time is 48 hours.

[0072] Step 3: After the obtained solid electrolyte material is cold pressed into finished product, the ionic conductivity at room temperature (25°C) is measured to be 2.76×10 -3 S / cm.

[0073] The cold pressing pressure is 20 MPa, and the obtained electrolyte sheet has a diameter of 13 mm and a thickness of 4 mm.

[0074] Comparative Example

[0075] This comparative example is a tantalum-free lithium zirconium oxychloride solid electrolyte and a synthesis method.

[0076] A tantalum-free lithium zirconium oxychloride solid electrolyte, comprising Li 1.75 ZrCl 4.75 O 0.5 .

[0077] A method for synthesizing a tantalum-free lithium zirconium oxychloride solid electrolyte comprises the following steps:

[0078] Step 1: In an argon-protected glove box, the lithium source and the zirconium source are ground and sieved respectively with a mortar to obtain 200-mesh raw material fine powder.

[0079] The lithium source is LiCl, and the zirconium source is ZrCl4 and ZrO2.

[0080] Step 2: In an argon-protected glove box, the sieved raw material fine powders are mixed and ball-milled in a ball mill according to the stoichiometric ratio to obtain an inorganic solid electrolyte Li 1.75-X ZlUT 0.2X Cl 4.75 O 0.5 powder.

[0081] The value of X is 0, and the inorganic solid electrolyte is Li 1.75 ZrCl 4.75 O 0.5

[0082] The molar stoichiometric ratio of LiCl, ZrCl4 and ZrO2 is 1.75:0.75:0.25;

[0083] The ball-to-material ratio of the ball mill is 30:1; the rotation speed of the ball mill is 600 rpm; and the ball milling time is 36 hours.

[0084] Step 3: After the obtained solid electrolyte material is cold pressed into finished product, the ionic conductivity at room temperature (25°C) is measured to be 2.38×10 -3 S / cm.

[0085] The cold pressing pressure is 20 MPa, and the obtained electrolyte sheet has a diameter of 13 mm and a thickness of 4 mm.

[0086] The ionic conductivity results of the inorganic solid electrolytes of the comparative example and each embodiment are shown in Table 1.

[0087] Table 1 Summary of test results of various inorganic solid electrolytes

[0088]

[0089]

[0090] The above embodiment of the present invention provides a tantalum-doped lithium zirconium oxychloride solid electrolyte and a synthesis method thereof. The provided tantalum-doped lithium zirconium oxychloride solid electrolyte is a new inorganic solid electrolyte, and the room temperature ion conductivity can reach 10 -3 S / cm, which is about 10 times higher than that of general metal oxide electrolytes. The manufacturing method is simple and the production cost is low, which is conducive to large-scale production and application.

[0091] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A tantalum-doped lithium zirconium oxychloride solid electrolyte, characterized in that: Its composition is Li 1.75- X ZlUT 0.2X Cl 4.75 O 0.5 ; The value range of X is 0<X≤0.

15.

2. A method for synthesizing the tantalum-doped lithium zirconium oxychloride solid electrolyte as claimed in claim 1, characterized in that: The following steps are involved: Step 1, under the protection of argon gas, the lithium source, the zirconium source and the tantalum source are respectively ground and sieved to obtain 200-mesh raw material fine powder; The lithium source is LiCl, the zirconium source is ZrCl4 and ZrO2, and the tantalum source is Ta2O5; Step 2: Under the protection of argon gas, the sieved raw material fine powder is mixed and ball-milled according to the stoichiometric ratio to obtain the inorganic solid electrolyte Li 1.75-X ZlUT 0.2X Cl 4.75 O 0.5 ; The value range of X is 0<X≤0.15; Step 3: After the obtained solid electrolyte material is cold-pressed into a finished product, the room temperature ionic conductivity is measured to be 2.41-3.12×10 -3 S / cm.

3. The method for synthesizing the tantalum-doped lithium zirconium oxychloride solid electrolyte according to claim 2, characterized in that: In step 1, the operation is carried out in a glove box protected by argon gas, and the grinding operation is performed using a mortar.

4. The method for synthesizing the tantalum-doped lithium zirconium oxychloride solid electrolyte according to claim 2, characterized in that: In step 1, the molar stoichiometric ratio of LiCl, ZrCl4, ZrO2 and Ta2O5 is 1.6-1.7: 0.7625-0.7875: 0.2125-0.2375: 0.005-0.

015.

5. The method for synthesizing tantalum-doped lithium zirconium oxychloride solid electrolyte according to claim 2, characterized in that: In step 2, the operation is carried out in a glove box protected by argon gas, and the sieved raw material fine powder is mixed and ball-milled in a ball mill.

6. The method for synthesizing tantalum-doped lithium zirconium oxychloride solid electrolyte according to claim 2, characterized in that: In step 2, the ball-to-material ratio of the ball mill is 15 to 60:1; The rotation speed of the ball mill is 200 to 1000 rpm; The ball milling time is 12 to 48 hours.

7. The method for synthesizing the tantalum-doped lithium zirconium oxychloride solid electrolyte according to claim 6, characterized in that: The ball-to-material ratio of the ball mill is 20 to 30:1; The rotation speed of the ball mill is 550-600 rpm; The ball milling time is 24 to 36 hours.

8. The method for synthesizing tantalum-doped lithium zirconium oxychloride solid electrolyte according to claim 2, characterized in that: In step 3, the cold pressing pressure is 20 MPa; The obtained electrolyte sheet had a diameter of 13 mm and a thickness of 4 mm.

Citation Information

Cited By

  • Halide solid electrolyte and preparation method and application thereof

    CN121922709A